2016
DOI: 10.1590/s1808-185120161503160596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prognostic Factors in Quality of Life of Patients With Adolescent Idiopathic Scoliosis Undergoing Spinal Fusion by the Posterior Approach

Abstract: Objective: To evaluate the prognostic factors in the treatment of patients diagnosed with adolescent idiopathic scoliosis undergoing spinal fusion by the posterior approach. Methods: The study included 48 patients with idiopathic adolescent scoliosis (43 females and 5 males) who underwent spinal fusion by the posterior approach, with an average age at diagnosis of 12 years, and clinical signs of Risser between 3 and 4 at the time of surgery. Clinical and radiographic measurements were performed, the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Scoliosis is a spinal deformity that can occur in varying degrees, bringing consequences and impacts to the lives of those affected and, thus, interfering in the quality of life of these individuals. 6 From the results obtained in this study, we observed agreement with scientific publications regarding the epidemiological data for scoliosis, since there was a higher prevalence of the disease in females, as well as greater involvement in the adolescent age group. These findings are justified by the fact that adolescent idiopathic scoliosis (AIS) is the most common type, accounting for up to 85% of cases, with onset usually after 10 years of age, and its predilection for females is explained by the fact that bone development occurs earlier among girls.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Scoliosis is a spinal deformity that can occur in varying degrees, bringing consequences and impacts to the lives of those affected and, thus, interfering in the quality of life of these individuals. 6 From the results obtained in this study, we observed agreement with scientific publications regarding the epidemiological data for scoliosis, since there was a higher prevalence of the disease in females, as well as greater involvement in the adolescent age group. These findings are justified by the fact that adolescent idiopathic scoliosis (AIS) is the most common type, accounting for up to 85% of cases, with onset usually after 10 years of age, and its predilection for females is explained by the fact that bone development occurs earlier among girls.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, complaints about appearance and behavioral and psychological changes are observed in all individuals with scoliosis. 6 In our study, the most affected quality of life domain was that of activity, followed by mental health. Regarding function, it is important to infer that the physical problem, the pain, and, in more advanced cases, the impairment of pulmonary and cardiac activity are relevant factors that hinder the participation of these individuals in social and physical activities, limiting their daily activities.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation